Is momentum due to data-snooping? - Johan Ericsson; Andrés González (Stockholm School of Economics, The Economic Research Institute (EFI), 2003)
This paper explores the profitability of portfolio-based momentum strategies. The data consists of all NYSE, AMEX, and NASDAQ stocks on the CRSP database. The analysis considers the period July 1963 to December 2002 and the tests are performed on portfolios formed on industry, size and book-to-market. The departure from earlier studies lies in the way we test for profitability. To avoid the serious problem of data-snooping we apply the procedure provided by White (2000). Overall, we find strong evidence of a momentum effect where an investor takes a long position on the winner portfolio and a short position on the loser portfolio. Hence, we reject the hypothesis of weak market efficiency. Splitting the sample in two parts, 1963:07 to 1981:12 and 1982:01 to 2002:12 we found that the best momentum strategy was profitable during the first period and not during the second. The overall significance is thus driven by events in the earlier part of the sample and it appears that the market has become more efficient.
Keywords: G11; G12; G14; 330; Momentum; Data-snooping; Bootstrap; Portfolio-Management; Momentenmethode